Reversing the Nucleophilicity of Active Sites in CoP2 Enables Exceptional Hydrogen Evolution Catalysis. Issue 14 (15th February 2022) - Niu, Shuwen; Fang, Yanyan; Rao, Dewei; Liang, Guangjie; Li, Senyang; Cai, Jinyan; Liu, Bo; Li, Jianming; Wang, Gongming
Abstract: Precisely constructing the local configurations of active sites to achieve on‐demand catalytic functions is highly critical yet challenging. Herein, an anion‐deficient strategy to precisely capture Ru single atoms on the anion vacancies of CoP2 (Ru‐SA/Pv‐CoP2 ) is developed. Refined structural characterizations reveal that the Ru single atoms preferably bind to the anion vacancy sites and consequently build a superior catalytic surface with neighboring CoP and CoRu coordination states for the hydrogen evolution reaction (HER) catalysis. The prepared Ru‐SA/Pv‐CoP2 nanowires exhibit an unprecedented overpotential of 17 mV at 10 mA cm –2 geo, and the corresponding mass activity is 52.2 times higher than the benchmark Pt/C catalyst at the overpotential of 50 mV. Theoretical analysis illustrates that the introduced Ru‐SAs can reverse electrons state distribution (from nucleophilic P sites to electrophilic Ru sites) and boost the activation of water molecules and hydrogen production. More importantly, such a construction strategy is also applicable for Pt single atom coupling, suggesting its generality in building catalytic sites. The capability to precisely construct active sites offers a powerful platform to manipulate the catalytic performance of HER catalysts and beyond. Abstract : An Ru single atom is precisely anchored on anion vacancies of CoP2 (Ru‐SA/Pv‐CoP2 ), which reverses the initial nucleophilicity of active sites to electrophilicity by regulating the local orbital hybridization. The d electron‐rich Ru‐SA/Pv‐CoP2 exhibits an unprecedented overpotential of 17 mV at 10 mA cm –2 geo for hydrogen evolution catalysis.